MOBLE APPLICATIONS IN THE PROCESS OF TEACHING ENGLISH - Isheryakova Joanna Rinatovna (Galaxy International Interdisciplinary Research Journal, 2023)
Unfortunately, at present, programs of linguistic education for non-linguistic areas inadequately reveal matters of organization a teaching foreign languages and the role of practical realization linguistic culture as one of the main factors of teaching and upbringing non-linguistic students. In order to accomplish a current goal mobile applications come to help teachers and students. This article is dedicated to reveal the educational role of mobile applications to teach English language to students. There are several popular mobile apps for learning English, some of which are they are: Quizlet, Lingualeo, Duolingo, Memrise. In order to know which of the mobile applications is in demand and which one has numerous positive aspect there was carried out a comparative analysis Duolingo and Quizlet apps using certain criteria.